How Sensitive Are Latin American Exports to Chinese Competition in the U.S. Market? - López-Córdova, J. Ernesto; Micco, Alejandro; Molina, Danielken (World Bank, Washington, DC, 2012)
This paper estimates the elasticity of substitution of U.S. imports using detailed trade data over the 1990-2003 period. The authors use a two-stage least squares framework in order to identify the elasticity parameter of interest. The authors use the elasticity estimates to assess the extent to which Latin American and Chinese goods compete in the U.S. market by providing forecasts of how alternative policy scenarios may affect exports to the United States. The analysis considers the following scenarios: (i) currency revaluation in China; (ii) elimination of U.S. tariffs on Latin American exports under a hemispheric free trade agreement; and (iii) the elimination of quotas on apparel and textile exports under the Multi-Fiber Agreement. The findings show that a 20-percent appreciation of the renminbi reduces Chinese exports to the United States by a fifth, although since other regions increase sales to that market (0.5 percent for Latin America), U.S. imports decline by only 1.7 percent. Hemispheric free trade would increase Latin America's exports to the United States by around 3 percent. The removal of the quotas would lead to a sharp increase in Chinese sales to the United States (40 percent), but Latin America would see its share of the U.S. market decline by around 2 percent (2.5 percentage points). China's gains would come mainly at the expense of other regions of the world.